2014
DOI: 10.7860/jcdr/2014/7352.3925
|View full text |Cite
|
Sign up to set email alerts
|

Giant Peritoneal Loose Body: A Case Report and Review of Literature

Abstract: A 52-year-old Indian male was presented to the surgical outpatient department with complaints of discomfort in lower abdomen and increased frequency of micturition, occasionally associated with urge incontinence. Patient was experiencing these symptoms, which were progressively increasing for a duration of six months. He did not complain of burning micturition, haematuria and other bowel symptoms. There was no significant past medical history. General physical examination, abdominal exam including per rectal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Therefore, it is normally not necessary to conduct a surgical intervention when a gPLB is only detected radiologically without concomitant symptoms. An important issue is to define its entity and to distinguish it from other manifestations, presenting with similar symptoms and imaging results, e.g., a benign or malignant intrabdominal tumor, tuberculous granuloma [2] or, as in our case, from a leftover foreign body [14] . As suggested by some authors [2] , [15] , repeated radiological investigations, e.g., sonography in varying patient’s body positions could be helpful to make the correct diagnosis.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Therefore, it is normally not necessary to conduct a surgical intervention when a gPLB is only detected radiologically without concomitant symptoms. An important issue is to define its entity and to distinguish it from other manifestations, presenting with similar symptoms and imaging results, e.g., a benign or malignant intrabdominal tumor, tuberculous granuloma [2] or, as in our case, from a leftover foreign body [14] . As suggested by some authors [2] , [15] , repeated radiological investigations, e.g., sonography in varying patient’s body positions could be helpful to make the correct diagnosis.…”
Section: Discussionmentioning
confidence: 88%
“…An important issue is to define its entity and to distinguish it from other manifestations, presenting with similar symptoms and imaging results, e.g., a benign or malignant intrabdominal tumor, tuberculous granuloma [2] or, as in our case, from a leftover foreign body [14] . As suggested by some authors [2] , [15] , repeated radiological investigations, e.g., sonography in varying patient’s body positions could be helpful to make the correct diagnosis. Allam et al additionally reported a case where a PLB could be distinguished from a malignant tumor by 18 F-FDG PET-CT [10] .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Sometimes the free body becomes attached to omentum and receives blood supply from it. 2,[4][5][6] Other possible sources are the omentum, fat tissue in the pancreas or autoamputated adnexa. 1,3,7 CT scan and MRI can be helpful to identify a giant PLB, but preoperative diagnosis is hard to achieve as it is difficult to distinguish these loose bodies from other abdominal benign lesions.…”
Section: Discussionmentioning
confidence: 99%
“…1 The first case was described by Littre in 1703. 6 We report a case of a giant PLB diagnosed serendipitously through CT scan. Exploratory laparotomy revealed a free round, whitish, egg-like mass between the intestinal loops with no identifiable attachments to the surrounding structures.…”
Section: Introductionmentioning
confidence: 97%